The Influence of Service Quality Dimensions on Customer Satisfaction Index (CSI) in CFM56 Engine Shop Visits: Case Study at PT. Burung Maintenance Facility - Muhammad Andrian Prayudha; Manahan Parlindungan Saragih Siallagan (Program Pascasarjana STIE Amkop Makassar, 2025)
This study analyzes the influence of service quality dimensions on the Customer Satisfaction Index (CSI) for CFM56 Engine Shop Visits at PT. Burung Maintenance Facility (BMF). In the competitive aviation MRO industry, maintaining high service quality is crucial for customer retention. This research aimed to identify which service areas most significantly impact CSI and to formulate targeted improvement strategies. Using a qualitative descriptive methodology, data was collected through in-depth interviews with five key customers and triangulated with historical CSI data from 2020-2025. The findings reveal that Turnaround Time (TAT) and Pricing are the most critical drivers of customer dissatisfaction, with the lowest CSI scores. While Service Quality and Alignment were perceived positively, Communication and Documentation required refinement. The study concludes that customer loyalty is strongly tied to improvements in TAT reliability and pricing transparency. It is recommended that BMF’s management prioritizes a corporate-wide TAT improvement initiative, invests in expanding in-house repair capabilities to control costs and delays, and implements a structured communication protocol with tiered SLAs and regular customer reporting to enhance service delivery and secure long-term competitiveness.